2013
DOI: 10.1088/1674-1137/37/12/128001
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transitions of multiferroic BiFeO 3

Abstract: Pressure-induced phase transitions of multiferroic BiFeO 3 have been investigated using synchrotron radiation X-ray diffraction with diamond anvil cell technique at room temperature. Present experimental data clearly show that rhombohedral (R3c) phase of BiFeO 3 first transforms to monoclinic (C2/m) phase at 7 GPa, then to orthorhombic (Pnma) phase at 11 GPa, which is consistent with recent theoretical ab initio calculation. However, we observe another peak at 2θ=7° in the pressure range of 5-7 GPa that has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…16,17 The R3c phase transforms to a monoclinic phase (space group: C2/m) at ∼3 GPa and then to a GdFeO 3 -type structure (space group: Pnma) at ∼12 GPa. 17 Zhang et al 18 also observed the C2/m phase at pressures 5−11 GPa. The reported Pnma phase confirmed the results of theoretical calculations.…”
Section: ■ Introductionmentioning
confidence: 90%
“…16,17 The R3c phase transforms to a monoclinic phase (space group: C2/m) at ∼3 GPa and then to a GdFeO 3 -type structure (space group: Pnma) at ∼12 GPa. 17 Zhang et al 18 also observed the C2/m phase at pressures 5−11 GPa. The reported Pnma phase confirmed the results of theoretical calculations.…”
Section: ■ Introductionmentioning
confidence: 90%
“…As hydrostatic pressure is applied at low temperatures, the rhombohedral R3c structure is expected theoretically to transform into the non-polar orthorhombic Pnma structure [65,66,[104][105][106]. The critical pressure was estimated variously between 3 and 20 GPa, whereas experimentally it was found to be ≈10 GPa [107][108][109]. At lower pressures, however, different groups identified a series of different phase transitions from the low pressure R3c to several orthorhombic or monoclinic structures.…”
Section: Introduction To Structurementioning
confidence: 99%
“…Interestingly, also the electric polarization of BFO connected to the R3c phase decreases with increasing pressure 22 and disappears above P c1 . [19][20][21][22][24][25][26][27][28] Additional studies are needed to elucidate the atomistic and electronic origin of the disappearance of the features above P c1 . During pressure release only feature A reappears at 1.1 GPa [see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 in Ref. 17), including orthorhombic 17,[19][20][21][22][23] , monoclinic [24][25][26] or a mixture 19,27,28 of various phases. The corresponding space group for the possible monoclinic symmetry was suggested to be C2/m and the orthorhombic phases were reported to exhibit Ima2, I2cm, I2cb, P bam, Ibam, Cmmm, P na2 1 or even P 222 1 symmetry.…”
Section: Introductionmentioning
confidence: 99%